Hyperhidrosis A Complete Guide to Diagnosis and Management (Springer International Publishing, 2018)
Hyperhidrosis is a medical condition in which a person sweats excessively and unpredictably. People with hyperhidrosis may sweat even when the temperature is cool or when they are at rest. Despite prevalence of at least 1% of the global population, Hyperhidrosis is still an unknown entity, for the most part -- an undertreated and even neglected medical condition. Moreover, there are few sources summarizing the knowledge on hyperhidrosis to a wider audience. The purpose of this book is to provide information regarding hyperhidrosis, ranging from basic information on pathophysiology to the most advanced therapeutic alternatives. From a therapeutic perspective, hyperhidrosis requires clinical treatment using topical and subdermal agents as well as surgical approaches. The book will not only cover these topics but will discuss all aspects of care -- from patient selection through post-surgical complications. Special attention will be given to sympathectomies. Medical and paramedical professionals, as well as students and researchers, interested in the topic will find the book comprehensive in scope and targeted in offering practical, clinical guidance. Diagnosis and Treatment of Hyperhidrosis - A Complete Guide counts with the collaboration of most renowned specialists of this field, and is intended as an easy to read and very practical reference book.